2018
DOI: 10.1186/s13013-018-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and patient satisfaction in bracing treatment of adolescent idiopathic scoliosis

Abstract: BackgroundBracing is used as a valid non-surgical treatment for adolescent idiopathic scoliosis (AIS) to avoid progression of the deformity and thereby surgery. The effect of bracing treatment on quality of life of patients with AIS has been a topic of interest in the international literature. The aim of this study was to evaluate the quality of life and patient satisfaction during bracing treatment for AIS of a pediatric hospital.Material and methodWe assessed a total of 43 non-consecutive female patients (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 78 publications
(67 reference statements)
1
40
0
1
Order By: Relevance
“…Results from this study are consistence with prior reports. 13 , 16 , 22 Rivett et al . studied the relationship between quality of life and brace compliance, and they found that poor compliance patients, wearing brace <20 hours/day, was associated with poorer QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from this study are consistence with prior reports. 13 , 16 , 22 Rivett et al . studied the relationship between quality of life and brace compliance, and they found that poor compliance patients, wearing brace <20 hours/day, was associated with poorer QOL.…”
Section: Discussionmentioning
confidence: 99%
“…24 Piantoni et al revealed that the majority of the patients (75%) in their cohort concerned about their social function during brace treatment and half of them had difficulties at school. 22 Donelly et al found that braced patients often had conflict with their parents over brace wearing and they thought that their classmates treated them differently. Some patients reported that when teachers taught about AIS in their class, it made their friends more open-minded and sympathy toward patients with AIS.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the increase in the SRS-22 score and the improvement of truncal shift and shoulder asymmetry are consistent. One of the biggest problems of conservative treatment of AIS is that patient compliance is low and patients who use a brace feel physiologically and psychologically sick [30]. Also, it has been reported in the literature that depression symptoms can be seen in patients who use a brace [31].…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 , 25 ] Living with braces still remains a potential ingredient of curvation and patients poor brace compliance [ 26 , 27 ] and can have a negative effect on patients psychological, motor, social, and school environment. [ 28 ]…”
Section: Introductionmentioning
confidence: 99%